Viscoelastography interpretation: Viscoelastography interpretation - Chavalertsakul, Karuna; Laikitmongkhon, Jakkrit (Clinical Critical Care, 2025)
The application of viscoelastography, which includes both Thromboelastography (TEG) and Rotational Thromboelastometry (ROTEM), has become increasingly prominent across various clinical disciplines. Its utility is well-documented in surgical settings, trauma care, postpartum care, and critical care medicine, where patients often experience complex and dynamic disturbances in hemostasis. Viscoelastic testing offers a rapid, real-time, point-of-care evaluation of the entire coagulation process, providing valuable insights into the distinct phases of clot initiation, clot strength, and subsequent fibrinolysis. The understanding and timely interpretation of viscoelastography results enhance the precision of hemostatic management by guiding the judicious use of appropriate blood components and hemostatic agents. This targeted approach reduces the risks associated with transfusion-related complications and contributes to improved overall clinical outcomes.